What is gastritis? What is gastropathy? How is it classified? - Kayaçetin, Serra; Güreşçi, Servet (Turkish Journal of Gastroenterology, 2014)
Abstract Stomach endoscopic biopsies are made to determine the diagnosis of the illness, its stage, and follow-up after the treatment. It is very significant to collaborate with the clinician while evaluating endoscopic biopsies. Besides the clinical and laboratory information of the patient, the endoscopic appearance of the lesion should be known. The clinician and pathologist should use the same language and the same terminology. Although new classifications have been made to prevent the confusion of terminologies in neoplastic processes recently, most centers around the world have reported non-invasive neoplasias without giving any certain diagnosis by just commenting on it. The clinician should understand what the pathologist wants to say; pathologists should know the approach of the clinician (repetition of the biopsy, endoscopic resection, surgery). There is Helicobacter pylori (HP) in most of the stomach pathologies as the etiologic agent. No matter if the factor is HP or other etiologic agents, the tissue gives similar responses. That is why clinical-endoscopic indications should be taken into consideration, as well as histological indications, and the reports of the endoscopy should be seen. A good clinicopathologic correlation increases the accuracy of the diagnosis.